A stock-flow consistent model of the portuguese economy - Sousa, Pedro Oliveira Pratas e (2016)
According to Olivier Blanchard, one of the silver linings of the 2007-2008 financial crisis has been to jolt macroeconomics and macroeconomic policy and to demonstrate some of the shortcomings of DSGE (Dynamic Stochastic General Equilibrium) models. In this thesis we tried to present an alternative or complementary approach to the referred models, an approach based on the stock-flow consistent models of Godley and Lavoie and on the complexity theory approach championed by Steve Keen. Its main characteristics are: the possibility of integration of the real economy with a well-developed financial sector; a holistic view of the economy, in which sectoral balances take center stage; the acknowledgement of the principle of fundamental uncertainty, rejecting the hypothesis of rational expectations; the recognition of the monetary nature of the economy, the role of debt and the endogeneity of money; and the rejection of the methodological equilibration of neoclassical theory with the economy being seen, instead, as basically in constant disequilibrium. Based on this principles we built a model of the Portuguese economy, in order to analyze the austerity policies applied in the last years in our country. In a first phase, our work consisted in building a benchmark model that replicated the 2008-2013 period. In a second stage, we changed some of the variables, recreating alternative scenarios and options, and analyzed the results obtained comparing them with the benchmark case. More than precise answers, the goal of this work is to contribute to an informed intuition of the functioning of the Portuguese economy.